Caracterização estrutural e eletroquímica de recobrimentos a base de óxido de grafeno aplicados sobre liga de NiTi superelástica - Athos Fernandes Araujo (2021)
The mechanical responses under superelastic loading cycles, and the corrosion protection capacity of two graphene-based coatings applied to a NiTi alloy were evaluated. Graphene oxide (GO) and a composite of reduced graphene oxide (RGO) incorporated in a block copolymer of styrene-ethylene-butylene-styrene (SEBS) were deposited on the substrate via dip-coating. The morphology of the coatings was characterized by scanning electron microscopy before and after uniaxial loading cycles up to 6%. Atomic force microscopy was also used to evaluate the roughness of the coatings. The corrosion behavior was studied by potentiodynamic polarization, electrochemical impedance spectroscopy, and Mott-Schottky analysis. The results showed that both GO and RGO+SEBS coatings presented the capacity of following several superelastic cycles and maintain their morphological integrity. However, only the RGO+SEBS coating showed a significant improvement in terms of corrosion resistance.